2009
DOI: 10.1111/j.1558-5646.2009.00639.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Mammal Tooth Patterns: New Insights From a Developmental Prediction Model

Abstract: The study of mammalian evolution is often based on insights into the evolution of teeth. Developmental studies may attempt to address the mechanisms that guide evolutionary changes. One example is the new developmental model proposed by Kavanagh et al. (2007), which provides a high-level testable model to predict mammalian tooth evolution. It is constructed on an inhibitory cascade model based on a dynamic balance of activators and inhibitors, regulating differences in molar size along the lower dental row. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
77
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 39 publications
8
77
2
Order By: Relevance
“…Second, the sequential development of the cheek tooth row is likely to be an integrated system, in which the development of molars and rudimentary buds is not independent. Recent articles have shown that during the first, second, and third molar sequential development, each developing molar exerts an inhibitory influence on the next developing molar (36,37). The present study suggests that this model should be extended to include the rudimentary buds that presumably represent premolars, meaning that the premolar rudiments would have an influence on patterning of molars (Fig.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Second, the sequential development of the cheek tooth row is likely to be an integrated system, in which the development of molars and rudimentary buds is not independent. Recent articles have shown that during the first, second, and third molar sequential development, each developing molar exerts an inhibitory influence on the next developing molar (36,37). The present study suggests that this model should be extended to include the rudimentary buds that presumably represent premolars, meaning that the premolar rudiments would have an influence on patterning of molars (Fig.…”
Section: Resultsmentioning
confidence: 67%
“…Therefore, earlier events (ED 10.5-12.0) should be responsible for the positioning of the MS, which might be the first of a cascade that patterns the whole tooth row. Such a cascade has already been suggested for the patterning of M1, M2, and M3 (10,36,37), and rudimentary buds could act in it, independently of their later fate. This result would be reminiscent of the situation known in fish, in which a pioneer tooth often sets the stage for the development of an entire row (38).…”
Section: Resultsmentioning
confidence: 70%
“…In accordance with the IC model, it should be possible to determine m3 size (5 product of mesiodistal and buccolingual measurements) by using m1 size, following the relationship m3 5 0.655m1 (Renvoisé et al 2009). Among the groups examined herein, for the multiple regressions (Table 2, parts A) a significant relationship between m3 and m1 size was found for ''Meridiungulata'' and Astrapotheria.…”
Section: Resultsmentioning
confidence: 99%
“…Hlusko et al (1) offer the example of the complex relationship between teeth and body size. Sexual dimorphism in size, including the dentition, is common in primates (18,19), but proportional tooth size is also linked to molecular genetic cascades of activators and inhibitors that produce sequences of molar teeth, and those proportions are linked to dietary function across a wide range of mammals, including primates (20)(21)(22)(23)(24). Selection for body size, sexual dimorphism, and dietary A B specialization can thus all have competing effects on primate dental traits (Fig.…”
mentioning
confidence: 99%